'a common idiom … call it a place'. Issue 1 (10th May 2019) - Jones, Tom
Abstract : Building on recent studies of the relationship between visual poetries and eco-poetics, this essay argues that language conceived of as systematic is an important consideration in the work of Thomas A. Clark. Beginning with readings of some of his meta-poetical work from the early 1970s, the essay suggests that the overt interest in poetic language as a system analogous to an ecosystem continues into Clark's later writing, though in a less overt, more ephemeralized manner. The essay explores ways in which Clark conceives of poetry as anti-entropic activity in a language system.